Creative Design Of Multipurpose Space On Pedestrian Sidewalks Case Study : Kaliurang Street, Yogyakarta - Rusadi, Emmy Yuniarti; Aditya, Rendy Bayu; Putrarinsi, Pasha Grata; Wibisono, Bambang Hari (Fakultas Teknik, Universitas Brawijaya, 2014)
Indonesia is a country with 54 million informal economic sector actors. Many sidewalks with street vendors have been researched to obtain the general phenomena of the informal sector. In the other hand, Indonesian government still has no considerable action to manage these cases. Kaliurang Street is one of the streets filled with informal sectors. the street is situated in the heart of Yogyakarta Agglomeration Area (YAA). More than IDR 200 million per year or approximately IDR 1,000 of retribution per day (minimumly) have been paid by street vendors to the local government. Physically, pedestrians need wider walking tracks and separators between walking activity and trading .There are four alternatives of intervention by combining the two needs of economic and pedestrian sidewalks function. Creative is not defined merely as an artistic thing anymore, but thinking out of the box in uncertainty problems solving. Multipurpose space in pedestrian sidewalks means space in pedestrian sidewalk that is used not only for pedestrian, but also activities of street vendor, while on street parking is definitely argued to be reduced. Furthermore, it is hopefully followed by more research about creative physical design in urban contexts in facing the informal economic sector realm as Indonesia will face forward.Keywords: Pedestrian Sidewalks, Multipurpose Space, Design